Proteasome Inhibitors Protect Against Degeneration of Nigral Dopaminergic Neurons in Hemiparkinsonian Rats - Masatoshi Inden; Jun-ichi Kondo; Yoshihisa Kitamura; Kazuyuki Takata; Kaneyasu Nishimura; Takashi Taniguchi; Hideyuki Sawada; Shun Shimohama (Elsevier, 2005)
Parkinson's disease is characterized by dopaminergic neuronal death and the presence of Lewy bodies in the substantia nigra pars compacta (SNpc). α-Synuclein and ubiquitin are components of Lewy bodies, but the process of Lewy body formation and the relationship between inclusion formation and dopaminergic neuronal death have not been resolved. In this study, unilateral intranigral microinjection of 6-hydroxydopamine caused a significant loss of tyrosine hydroxylase-immunopositive neurons in both the substantia nigra and striatum and apomorphine-induced contralateral rotation. The co-administration of proteasome inhibitors, such as lactacystin or carbobenzoxy-L-leucyl-L-leucyl-L-leucinal (MG-132), significantly prevented both dopaminergic neurodegeneration and apomorphine-induced rotational asymmetry. Proteasome inhibitors markedly formed intracellular protein inclusions labeled by thioflavin-S in the SNpc. Inclusion-like immunoreactivities for α-synuclein and ubiquitin were detected after 4 weeks. These results suggest that proteasome plays an important role in both the early phase of dopaminergic neuronal death and inclusion body formation. Keywords:: proteasome inhibitor, neuroprotection, dopaminergic neuron, substantia nigra, Parkinson's disease